Room temperature synthesis of triazine covalent organic frameworks for size-selective intercalation of molecules and fast water purification - Salahvarzi, Maryam; Setaro, Antonio; Beyranvand, Siamak; Nemati, Mohammad; Gordeev, Georgy; Fiebor, Alphonse; Ludwig, Kai; Ghanbari, Reza; Nasiri, Nima; Ahmadi, Vahid; Weber, Manuela; Jamshidi, Zahra; et al. (Materials today. Chemistry, 2024)
In this work, we report on a new method for the construction of triazine covalent organic frameworks on gram scale by catalyst-free cyclotrimerization of alkynes at room temperature for the size-selective intercalation of molecules and fast water purification. Reaction between sodium acetylide and cyanuric chloride resulted in 2,4,6-triethynyl-1,3,5-triazine intermediate which converted to heteroaromatic frameworks comprising triazine and benzene rings upon in situ [2 + 2+2] cyclotrimerization. Mechanistic studies revealed a crucial role for the triazine ring in susceptibility of ethynyl groups to cyclization. The permeability of these nanostructures to small molecules, exemplified by Rhodamine 6G (R6G) and HAuCl4, and their impermeability to bigger objects such gold nanoparticles (5 nm) indicated their potential to remove molecular impurities from water. Impurities including Methylene blue and Malachite green with 20 mg L−1 concentration were completely removed by 1 mg of the synthesized frameworks in 60 s. Taking advantages of the straightforward synthesis and permeability to small molecules, the synthesized triazine frameworks can be used for the fast and efficient purification of water contaminated by toxic agents.
Gesehen am 07.02.2025